Health-related quality of life in a PD-First programme in South Africa - Davidson, Bianca; Welgemoed, Waldo; Jones, Erika; Barday, Zibya; Manning, Kathryn; Wearne, Nicola (African Journal of Nephrology, 2020)
Groote Schuur Hospital in Cape Town, South Africa, offers a PD-First policy as a result of haemodialysis (HD) restrictions and resource limitations. This study aimed to compare health-related quality of life (HRQOL) between HD and peritoneal dialysis (PD) patients, given the lack of autonomy in modality choice and the socio-economic challenges. This single-centre, cross-sectional study was performed between July 2015 and December 2016. Demographic, socio-economic variables and perceptions of safety were collected. HRQOL was assessed using the Kidney Disease Quality of Life-Short Form (KDQOL-SFTM) version 1.3. All data were compared between the two dialysis modalities; 77 HD and 33 PD patients were included in the study and there were no significant differences in demographics. Median age was 42.5 years (IQR: 32.4–48.6) and 57.3% were female. HD patients had less pain (P = 0.036), better emotional well-being (P = 0.020) and a better energy/fatigue score (P = 0.015). Both cohorts experienced role-limitations due to physical health with PD being more affected overall (P = 0.05). The only significant symptom in the kidney domain was that PD patients experienced more shortness of breath (P < 0.001). Patients in both groups had very poor socio-economic circumstances, and safety within their communities was a major concern. The patients in our dialysis service have very challenging social circumstances. Those on PD scored worse in four HRQOL domains, possibly due to a lack of autonomy in dialysis modality choice and less frequent contact with dialysis staff. Additional psychological and social support needs to be instituted to help improve our patients’ well-being on PD.